2001
DOI: 10.1063/1.1328417
|View full text |Cite
|
Sign up to set email alerts
|

Structure of alkali tellurite glasses from neutron diffraction and molecular orbital calculations

Abstract: The structure of pure TeO 2 and alkali tellurite glasses has been examined by neutron diffraction and ab initio molecular orbital methods. The experimental radial distribution functions along with the calculated results have demonstrated that the basic structural units in tellurite glasses change from highly strained TeO 4 trigonal bipyramids to more regular TeO 3 trigonal pyramids with increasing alkali content. It has also been shown that the TeO 3 trigonal pyramids do not exist in the form of isolated units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 25 publications
(24 reference statements)
2
27
0
Order By: Relevance
“…Molecular orbital calculations have also been performed for cluster models of sodium tellurite glasses [4] and Na-O coordinations of 3, 4 and 5 were found. It was concluded that the 5-coordinated environment is more representative of the glass, based on the results of the previous 23 Na NMR study [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular orbital calculations have also been performed for cluster models of sodium tellurite glasses [4] and Na-O coordinations of 3, 4 and 5 were found. It was concluded that the 5-coordinated environment is more representative of the glass, based on the results of the previous 23 Na NMR study [11].…”
Section: Introductionmentioning
confidence: 99%
“…The local structure of alkali M2O-TeO2 glasses (M = Li, Na, and K) has been studied extensively using neutron diffraction [1][2][3][4][5], X-ray diffraction [6,7], EXAFS [7,8], Raman scattering [7,9,10], NMR [2,[11][12][13] and RMC modelling [2,14]. In these studies, particular emphasis was placed on determining the local environment of tellurium and there is a general consensus that the average tellurium coordination number, nTeO, decreases as an oxide modifier is added to the glass network, the change being driven by the bonding requirements of the modifier.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there exist a large amount of literature regarding the structure of pure TeO 2 and xM 2 O-(1-x)TeO 2 (M 2 O: alkali oxide, x: mole fraction) glasses with a variety of techniques such as X-ray diffraction [6][7][8], neutron diffraction [8,9], NMR [10][11][12], Mösbauer spectroscopy [13], EXAFS [14], ab initio quantum-mechanical calculations [15,16], molecular orbital calculations [9], Brillouin [17], IR [ 18,19] and Raman scattering [20][21][22][23]. However, a limited number of papers have been focused on binary glassy systems where both components are glassformers participating directly in the formation of the vitreous network.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported or ganicinorganic hybrid lowmelting glasses prepared from a nonaqueous acidbase reaction in our previous papers. 1)3) The hybrid glass precursor consisting of Si(Me) 2 OP framework was prepared through a nonaqueous acidbase polycondensation reaction of POH{SiCl¨POSi{ HClª from the mixtures of orthophosphoric acid H 3 PO 4 and dialkyldichlorosilane R 2 SiCl 2 . 1) Based on this reaction, we prepared organicinorganic hybrid lowmelting glasses SnOMe 2 SiOP 2 O 5 , 2) of which T g 's were ranging from |25 to 50 C. Detailed structure of the glasses was also examined by 29 Si MAS NMR spectroscopy and ab initio molecular or bital (MO) calculations.…”
Section: Introductionmentioning
confidence: 99%